Unveiling Business Zakat Compliance: A Systematic Review of Determinants and Influential Factors - Nor-Ahmad, Saidatul Nurul Hidayah Jannatun Naim; Sulaiman, Aryati Juliana; Rahman, Rusniza Abdul; Shafai, Nor Atikah; Osman, Mohd Farihal (Indian Journal of Information Sources and Services, 2025)
Purpose: This systematic literature review (SLR) investigates the determinants influencing business zakat compliance, synthesizing findings from 15 peer-reviewed studies from Scopus and Web of Science. By identifying psychological, socio-economic, institutional, and religious factors affecting compliance behaviour, this review aims to bridge research gaps and provide insights for policymakers, zakat institutions, and business stakeholders.